Land use types and soil pH co-mediate bacterial community assembly processes: Application of the neutral community model and null model to determine stochastic and deterministic processes in a subtropical basin, China - Jinquan Huang; Yujie Qi; Die Chen; Jigen Liu; Li Li; Wenjie Zhang; Xiaolan Liu; Weiwen Li; Zhichao Mao (Ecological Indicators)
Land use regimes strongly impact bacterial microbial communities. However, the ecological processes shaping bacterial community assembly under various land use types and the factors altering the balance between these processes remain poorly understood. To address these knowledge gaps, we investigated bacterial community assembly processes in four different land use types (paddy fields, forests, sloping fields and garden plots) within the Dongting Lake Basin (a subtropical region in China) using the neutral community model (NCM), null model, and high-throughput sequencing datasets. Among the tested land use types, bacterial communities in paddy fields exhibited the highest species richness (mean Sobs: 3695±495) and diversity (mean Shannon: 6.933±0.241), and had a significantly higher stochastic process contribution (71.9%) as well as greater migration rates (Nm=4922). In contrast, bacterial communities in forests and sloping fields were mainly governed by deterministic processes (50.1% and 56.1%, respectively), especially variable selection. Garden plots exhibited intermediate characteristics, with stochastic processes (64.7%) dominated by homogenizing dispersal. Redundancy analysis (RDA) identified soil pH as the strongest environmental factor influencing bacterial community structure (57.0% explanatory power, p<0.01). Under acidic soil conditions (pH≤ 5.5), microbial assembly processes were more stochastic and driven primarily by homogenizing dispersal, whereas under neutral conditions (pH 5.5–8.5), deterministic processes, especially variable selection, dominated. In summary, homogenizing dispersal and variable selection primarily drive soil bacterial community assembly, with their relative importance being co-mediated by land use types and soil pH. By revealing the key mechanisms regulating soil bacterial assemblages under different agricultural practices and environmental conditions, our study offers farmers with strategies to enhance soil health through informed land management, assists policymakers in devising effective agricultural policies, and underscores the broader societal significance of conserving agroecosystems for environmental and economic stability.